Determinants of Inclusive Growth in Java: Evidence from District-Level Panel Data (2019–2023) - I Wayan Suparta; Mairizal Salehudin Siatan; Marselina Marselina; Hanif Hanif (SCAD Independent, 2026)
This study aims to examine the patterns and determinants of inclusive economic growth across districts and cities in Java Island by explicitly accounting for regional structural heterogeneity. Using secondary panel data from 23 regencies/cities over the period 2019–2023, the analysis employs panel data regression within the Klassen Typology framework to distinguish between developed and rapidly growing regions and developed but depressed regions. The findings indicate that economic growth consistently contributes positively to inclusive growth across regions, although its magnitude varies by regional typology. Human capital, financial inclusion, employment opportunities, and road infrastructure are found to enhance inclusiveness in both regional groups, while income inequality persistently constrains inclusive outcomes. Poverty significantly reduces inclusiveness only in developed and rapidly growing regions, whereas sanitation infrastructure plays a more prominent role in supporting inclusive growth in structurally constrained regions. These results demonstrate that inclusive growth mechanisms are context-dependent and region-specific, highlighting the limitations of uniform development policies. By integrating district-level panel data with a regional typology approach, this study contributes to the inclusive growth literature by emphasizing the importance of structural differentiation in translating economic growth into equitable development outcomes.